A Study on the Impact of Verse in the Metaverse: Exploring the Role of Avatars in Scientific Storytelling - Mehboob, Saima; Fornasari, Alberto; Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2025)
The current research focuses on the effects of Avatar-Based Storytelling within a metaverse-type environment on the learning performance, engagement, and emotional-social experience of primary school students within science education. In Poland, a quasi-experimental pre-test post-test control group design was used with 50 students aged between 8 and 12. Because it was conducted on an experimental basis, the first group experienced a two-week intervention, in which avatars used interactive science scripts, while the second group interacted with the same content via conventional digital media. The results of pre- and post-tests, as well as the engagement survey, showed that learning and engagement in the experimental group improved significantly (p < .001). Data from the focus group interviews in the form of qualitative results showed that the participants perceived avatars positively as credible and relatable characters that evoked emotions. The findings contribute to the positive view that short-term avatar-based narratives can support improvements in cognitive performance, motivation, and emotional bonding of virtual learning contexts. Discussions on the implications of immersive pedagogy and directions for future longitudinal research are provided.